Strain gauge evaluation of bone microstrain in full-arch implant-supported prostheses: cobalt-chromium and fiberglass materials - de OLIVEIRA, William Simões [UNESP]; de Oliveira, Mariana Simões; Carvalho, Alinne Siqueira [UNESP]; Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP]; Bottino, Marco Antonio [UNESP]; Nogueira Júnior, Lafayette [UNESP] (Editora Cubo, 2024)
Objective: This study addresses the strain gauge evaluation of bone microstrain in full-arch implant-supported prostheses using two distinct materials: Cobalt-Chromium (CoCr) and Fiber Reinforced with Composite (FRC). Material and methods: By employing strain gauge analysis, this study compares the mechanical properties of CoCr and FRC, noting that FRC bars exhibit significantly smaller microstrain under load, suggesting a more balanced strain distribution. Results: This finding may be attributed to the intrinsic material properties of each, where FRC offers relative flexibility and a modulus of elasticity closer to that of human bone tissue, promoting harmonious integration with peri-implant tissue. Additionally, the potential toxicity of CoCr alloys is addressed, emphasizing the importance of alternative materials that minimize health risks. Conclusion: This study contributes to the field of implant-supported rehabilitations, suggesting that FRC may offer significant mechanical and biocompatible advantages over CoCr. However, it underscores the need for further research to validate these findings.
Avaliação extensométrica de microdeformações ósseas em prótese implanto-suportada de arco completo: materiais cobalto-cromo e fibra de vidro
Keywords: Cobalt-chromium alloys; Dental prosthesis, Implant-supported; Elastic modulus; Fiberglass; Osseointegration